2018
DOI: 10.14715/cmb/2018.64.11.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 6-week zinc supplement and weight training on the blood lipids of the sedentaries and athletes

Abstract: In this study, we aimed to investigate the effect of 6 weeks of zinc supplementation and weight training on blood lipids of sedentary and athletes.Research group consists of total 40 males; 20 athletes who do regularly physical exercises and 20 sedentary volunteers. The volunteers were divided into four groups. These groups were constituted in that way: the first group is a natural sedentary group which called control group as well (S); the second group is another sedentary group which is supplied with only zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Furthermore strength is an important component for performance. Strength training affects some parameters that related to health as well as performance [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore strength is an important component for performance. Strength training affects some parameters that related to health as well as performance [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The timing of supplementation may also be important, with some studies suggesting that pre-exercise supplementation may be more effective in reducing oxidative stress compared to during or after exercise [ 222 ]. Additionally, the duration of treatment may play a role, as zinc supplementation for at least 4–6 weeks has been shown to improve antioxidant status in athletes [ 224 ].…”
Section: Key Points and Strategies For Antioxidant Supplementation In...mentioning
confidence: 99%
“…Regarding Zn supplementation, prior research has shown that Zn supplementation reduced blood viscosity [6], being inconsistent with the increase in VO 2peak in active young adults [18]. Similarly, Zn supplementation could have indirectly contributed to the improvement of sports performance by positively modifying blood lipid levels [19]. Therefore, given that Zn requirements in athletes may be different and given the variability of exercise-induced responses, there is a need not only for Zn assessment but also the activity of proteins related with Zn to establish and clarify relationships with sports practice.…”
Section: Introductionmentioning
confidence: 99%